FORMATION OF FINANCIAL LITERACY OF STUDENTS IN MATHEMATICS LESSONS (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the issue of the formation of financial literacy of students of secondary schools. Ways to increase financial literacy are presented.